CHARACTER EDUCATION VALUES IN THE ELEMENTARY SCHOOL ENGLISH TEXTBOOK ENTITLED “BASIC ENGLISH” FOR GRADE SIX - Windy Ayu Andini Rebowo Hadi; Mukminatus Zuhriyah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
One of the most important teaching materials is textbook. It is also inseparable from learning English in elementary school. Using English textbook in Elementary school to help a teacher in conveying material to their students. Textbooks that are suitable for use as teacher handbooks are those that are in accordance with the competency standards set by the ministry of education. The aims of the research are to analyze: the values of character education as reflected in the sixth grade English textbook of elementary school entitled